1984
DOI: 10.1148/radiology.153.3.6093191
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the diagnosis of breast disease: use of transverse relaxation times.

Abstract: The ability of magnetic resonance imaging (MR) to demonstrate breast carcinoma depends upon significantly different relaxation times in benign and malignant tissues. The authors conducted an in vitro study of transverse relaxation times (T2) of 393 breast tissue samples in order to establish a range of values for normal tissue, benign lesions, and carcinoma. All T2 values were multiexponential. Benign lesions were readily distinguished from both invasive and noninvasive carcinoma in samples containing fat or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 0 publications
2
12
0
2
Order By: Relevance
“…The question also arises whether our findings are consistent with previous relaxation measurements of breast tissue (2,5,6,27,28) or adipose tissue (16,29). Such comparisons are confounded by differences in the magnetic field strength and temperature at which measurements were performed (both influence T, and T, relaxation times) and by the methods by which relaxation times are measured and estimated.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The question also arises whether our findings are consistent with previous relaxation measurements of breast tissue (2,5,6,27,28) or adipose tissue (16,29). Such comparisons are confounded by differences in the magnetic field strength and temperature at which measurements were performed (both influence T, and T, relaxation times) and by the methods by which relaxation times are measured and estimated.…”
Section: Discussionsupporting
confidence: 87%
“…At present, the MR properties of normal and pathological breast tissue have been incompletely characterized, partly because breast tissue is a heterogeneous mixture of adipose and fibroglandular tissue at both macroscopic and microscopic resolution. Techniques to analyze and interpret measurements of MR relaxation times have improved significantly, however, since the T , and T, relaxation properties of breast tissue were last investigated extensively (5,6). Algorithms that interpret relaxation data in terms of continuous distributions of relaxation times, such as T2NNLS (7), provide a more realistic model of tissue heterogeneity than that previously provided by fits of relaxation data to a sum of several exponentials (8).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion‐weighted imaging is routinely employed in breast MRI as a quantitative measure of tissue cellularity, while dynamic contrast‐enhanced MRI is primarily used as a semiquantitative perfusion technique in breast imaging. Measurement of T 1 and T 2 relaxation times can provide additional information about normal and diseased breast tissue . Previous studies on breast relaxometry have observed significant differences in T 1 and T 2 relaxation times between normal fibroglandular breast tissue and benign and malignant breast tumors .…”
mentioning
confidence: 99%
“…Measurement of T 1 and T 2 relaxation times can provide additional information about normal and diseased breast tissue. 4,5 Previous studies on breast relaxometry have observed significant differences in T 1 and T 2 relaxation times between normal fibroglandular breast tissue and benign and malignant breast tumors. 5,6 Changes in T 2 relaxation time has also been used to characterize response to chemotherapy in breast cancers.…”
mentioning
confidence: 99%
“…T2WI are typically used to identify and characterize cysts. Typical breast carcinomas have shorter T2 relaxation times and display lower signal intensity (SI) on T2WI than benign lesions (16, 17). However, many benign lesions and some carcinomas, including mucinous (colloid) carcinomas (18), have a long T2 relaxation time and are occasionally difficult to distinguish from cysts on T2WI alone.…”
mentioning
confidence: 99%